THE ROLE OF THE AMOUNT OF MONEY IN RISK-TAKING - Nagy, Viktor (Copernican Journal of Finance & Accounting, 2017)
Decisions based on the expected value have two components: the probability and the value or utility that is often expressed in money. Regarding the first element, it can be pointed out that many decisions contain risk concerning the outcomes of the available options, i.e. concerning the probability of the occurrence of an event. Uncertainty refers, in most cases, to this part, but having said that, the second part, the amount of money, still matters in a decision-making situation. Since the research of the effect of the amount can be considered neglected compared to that of probabilities, I focused on the second component: on the role of the amount of money. The aim was to explore to what extent a 300 times difference in the amount affects the choice.